An Analytical Study of Cross Subsidy Impact on Electricity Demand from Industries: Case of Electricity Distribution Utilities in India - Agarwal, Naveen; Anwer, Naqui (International Journal of Energy Economics and Policy, 2019)
In India, because of socio-economic constraints, there is cross subsidy regime in electricity sector under that industrial consumers cross subsidize agricultural and residential consumers. This paper attempts to analyze the impact of cross subsidy on the industrial demand from the state distribution units. To measure the impact, elasticity of electricity demand in context of cross subsidy is estimated and to estimate cross subsidy elasticity, panel data techniques are used. The main finding of the paper is that the impact of cross subsidy on the Discom’s industrial load in is limited. The elasticity value of cross subsidy is -0.54, which is significantly lower than 1 (the perfectly elastic value), which means that change in cross subsidy does not have any meaningful influence on the electricity demand of the industrial consumers. Keywords: Cross Subsidy, Open Access, Electricity Demand JEL Classifications: H2, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8111